2012
DOI: 10.3171/2012.2.jns111360
|View full text |Cite|
|
Sign up to set email alerts
|

Dual regeneration of muscle and nerve by intravenous administration of human amniotic fluid–derived mesenchymal stem cells regulated by stromal cell–derived factor-1α in a sciatic nerve injury model

Abstract: Amniotic fluid-derived mesenchymal stem cells can be recruited by expression of SDF-1α in muscle and nerve after nerve crush injury. The increased deposition of AFMSCs paralleled the expression profiles of SDF-1α and its receptor CXCR-4 in either muscle or nerve. Administration of AFMSCs led to improvements in neurobehavior and expression of regeneration markers. Intravenous administration of AFMSCs may be a promising alternative treatment strategy in peripheral nerve disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 27 publications
3
38
0
Order By: Relevance
“…However, in the absence of cells, attempts to replicate the structural complexity of the nerve have led to disappointing results. Recent evidence exists that systemic administration of stem cells following peripheral nerve injury can be efficacious ( Figure 2E) [5,114] . With further refinement, it may become possible to sustain regenerative support through regular systemic dosing.…”
Section: Cell Scaffolds and Methods Of Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the absence of cells, attempts to replicate the structural complexity of the nerve have led to disappointing results. Recent evidence exists that systemic administration of stem cells following peripheral nerve injury can be efficacious ( Figure 2E) [5,114] . With further refinement, it may become possible to sustain regenerative support through regular systemic dosing.…”
Section: Cell Scaffolds and Methods Of Deliverymentioning
confidence: 99%
“…Stromal cell-derived factor-1α (SDF-1α) is chemotactic towards MSCs and is expressed in several tissues in the rat, including injured nerve. By timing intravenous administration of AFDSCs with peak expression of SDF-1α, this novel approach has been shown to improve AFDSC numbers at the repair site and nerve regeneration [114] . Fetal tissue represents a promising alternative source of stem cells.…”
Section: Bone Marrow Derived Stem Cellsmentioning
confidence: 99%
“…25,29,33,34,49,55 It has been found that pre-differentiation of stem cells into the Schwann cell phenotype in vitro prior to injection results in remarkably better outcomes compared with the use of undifferentiated SKPs or mesenchymal stem cells. 16,47,48 In previous studies, we and others showed that SKPs, predifferentiated in vitro into Schwann cells (SKP-SCs), survived in vivo and promoted robust axonal regrowth both in vitro and in acute and chronic models of rodent nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokines with chemokine receptors CXCR3, CXCR4 and CXCR6 were identified as the key players responsible for cell homing [44]. Further, CXCR4 ligands such as stromal cell-derived factor-1a (SDF-1a) promote MSCs' migration to the injury site [45]. Apart from migration and homing, recent studies have focused on cell free approaches such as EV [46].…”
Section: Mscs and Bpdmentioning
confidence: 99%